Evaluation of High-Protein Distillers Dried Grains on Growth Performance and Carcass Characteristics of Growing-Finishing Pigs - Z. X. Rao; R. D. Goodband; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; H. I. Calderón; M. F. Wilken (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 1,890 growing-finishing pigs (PIC; 359 × 1050; initially 59.8 ± 1.3 lb) were used in a 124-d growth trial to compare the effects of high-protein distillers dried grains (HPDDG) or conventional distillers dried grains with solubles (DDGS) on growth performance and carcass characteristics. Conventional DDGS contained 29.0% CP, 0.48% standardized ileal digestible (SID) Lys, and 9.2% oil, whereas HPDDG contained 39.3% CP, 0.68% SID Lys, and 11.1% oil. All diets were formulated on an equal SID Lys-basis with diets containing HPDDG having less soybean meal than diets with conventional DDGS. There were 27 pigs per pen and 14 pens per treatment. Treatment diets were corn-soybean meal-based and arranged in a 2 × 2 + 1 factorial with main effects of DDG source (conventional DDGS or HPDDG) and level (15 or 30%). A corn-soybean meal-based diet served as the control and allowed linear and quadratic level effects to be determined within each DDG source. Pens of pigs were assigned to 1 of the 5 treatments in a randomized complete block design with initial weight as a blocking factor. Data were analyzed using the lme4 package in R (version 3.5.2) with pen as experimental unit. Overall, there were no differences observed in ADG between pigs fed either DDG source or level. Pigs fed HPDDG had decreased (linear,P<0.001) ADFI and improved F/G compared with those fed conventional DDGS. Increasing either conventional DDGS or HPDDG decreased carcass yield and HCW (linear,P<0.02); however, there were no differences between pigs fed HPDDG or conventional DDGS. Iodine value (IV) was greater (P<0.001) in pigs fed HPDDG than conventional DDGS, and IV increased (linear,P<0.02) with increasing DDG source. In summary, these data suggest that pigs fed HPDDG had better F/G, but greater IV compared with pigs fed conventional DDGS, probably due to the difference in oil content.
Keywords: distillers dried grains with solubles; finishing pigs; high protein distillers dried grains